Evaluation of the Management Control System for the Profit Responsibility Center at PT. Cahaya Bintang Medan Furniture Tbk - Nadratul Hasanah Lubis; Murinanda Amalya Parinduri; M. Rifki Akbar (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study is to determine the management control system for the profit responsibility center of PT. Starlight Medan Furniture. The analysis method used is descriptive analysis. The results of the analysis show that the control of the profit center management at PT. Cahaya Bintang Medan Furniture has fulfilled one of the characteristics of liability accounting, namely the identification of profit liability centers. Implementation of control of the management of the profit responsibility center at PT. Cahaya Bintang Medan Furniture is adequate, this can be seen from the recording and authorization for adequate cost expenditures and the calculation of financial statement analysis, and can be used as a management tool in controlling the profit center with costs as a controlling tool.